2012
DOI: 10.1007/s10461-012-0321-z
|View full text |Cite
|
Sign up to set email alerts
|

Is the US AIDS Drug Assistance Program Cost-effective?

Abstract: Each year, the US AIDS Drug Assistance Program provides access to prescription drugs—including antiretrovirals—to more than 110,000 persons living with HIV (PLWH) who lack adequate medical insurance. PLWH on effective antiretroviral therapy live longer lives, with enhanced quality of life, and are less likely to transmit HIV to others. There are thus significant benefits associated with the ADAP program. But there also are substantial costs. A mathematical model was used to assess the cost-effectiveness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 18 publications
4
80
3
Order By: Relevance
“…For every one-unit increase in HFIAS score, there was a 0.6% unit decrease in CD4%.This inverse association replicates the only other report to include pediatric patients on the association of food insecurity and CD4 counts among HIV+ adolescents and young adults in the US. 16 This inverse association between food insecurity and CD4% was also consistent with multiple previous studies among low-income HIV+ adult populations in the US and Canada. 8-13 Altogether, there is a growing body of observational studies: (1) that indicate food insecurity as a potential negative influence on HIV clinical outcomes and (2) that the HFIAS instrument may be a useful screening method to identify food insecure HIV+ individuals and target them for food supplementation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For every one-unit increase in HFIAS score, there was a 0.6% unit decrease in CD4%.This inverse association replicates the only other report to include pediatric patients on the association of food insecurity and CD4 counts among HIV+ adolescents and young adults in the US. 16 This inverse association between food insecurity and CD4% was also consistent with multiple previous studies among low-income HIV+ adult populations in the US and Canada. 8-13 Altogether, there is a growing body of observational studies: (1) that indicate food insecurity as a potential negative influence on HIV clinical outcomes and (2) that the HFIAS instrument may be a useful screening method to identify food insecure HIV+ individuals and target them for food supplementation.…”
Section: Discussionsupporting
confidence: 90%
“…6,14,15 A similar study among adolescents and young adults reported an inverse association between food insecurity and CD4 counts among HIV+ patients at Texas Children's Hospital in Houston, USA. 16 Building on these previous reports, studies are necessary examining the relationship between food insecurity and CD4% among young children, who may be especially vulnerable to the effects of food insecurity due to their dependence on caregivers for food and their unique nutritional needs. Moreover, pediatric studies are necessary in Sub-Saharan Africa, where food insecurity and HIV are highly prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Enrollment and baseline characteristics are described elsewhere [12]. We screened 971 individuals of whom 728 (N=364 couples) met eligibility criteria and completed the baseline assessment.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the CDC funds programs for expanded and routine HIV testing and linkage to care [83]. Additionally, under the Health Resources and Services Administration's (HRSA) Ryan White program, the AIDS Drug Assistance Program (ADAP) provides lifesaving ART to those who cannot afford it, saving lives and averting transmissions and outreach services for persons who have fallen out of care, and Medical Case Management to increase treatment adherence [84]. Continued evaluation of these programs and collaboration between CDC and HRSA will be key to determining their effectiveness and impact on HIV surveillance outcomes.…”
Section: Implications/future Researchmentioning
confidence: 99%